The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s12041-017-0749-z
|View full text |Cite
|
Sign up to set email alerts
|

Single-nucleotide polymorphism of INS, INSR, IRS1, IRS2, PPAR-G and CAPN10 genes in the pathogenesis of polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) is the most common and a complex female endocrine disorder, and is one of the leading cause of female infertility. Here, we aimed to investigate the association of single-nucleotide polymorphism of INS, INSR, IRS1, IRS2, PPAR-G and CAPN10 gene in the pathogenesis of PCOS. A hospital-based, observational case-control study was carried on 169 PCOS and 169 control women in the southern region of India. Genotype was carried out by real-time polymerase chain reaction. A chi-square (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…In a small study from Hyderabad, 15 single-nucleotide polymorphisms (SNPs) from nine type 2 diabetes-related genes (such as TCF7L2, IGF2BP2, SLC30A8, HHEX, CDKAL1, CDKN2A, IRS1, CAPN10 and PPAR-γ ) were studied in PCOS women and controls; no significant association was found; the authors cited studies from other ethnic populations and suggested that the non-association might be universal47. Gly972Arg SNP of IRS1 was found to have a positive association with PCOS in a south Indian study population, whereas INS, IRS2, PPAR-γ and CAPN10 failed to show any association in the same study from Chennai48. Insulin receptor gene polymorphism was studied later49, for its association with IR in Indian women with PCOS; the study suggested that CC genotype (C1085T) might be developed as a marker for IR and metabolic complications in Indian women48.…”
Section: Studies In the Genetics Of Pcos From Indiamentioning
confidence: 97%
“…In a small study from Hyderabad, 15 single-nucleotide polymorphisms (SNPs) from nine type 2 diabetes-related genes (such as TCF7L2, IGF2BP2, SLC30A8, HHEX, CDKAL1, CDKN2A, IRS1, CAPN10 and PPAR-γ ) were studied in PCOS women and controls; no significant association was found; the authors cited studies from other ethnic populations and suggested that the non-association might be universal47. Gly972Arg SNP of IRS1 was found to have a positive association with PCOS in a south Indian study population, whereas INS, IRS2, PPAR-γ and CAPN10 failed to show any association in the same study from Chennai48. Insulin receptor gene polymorphism was studied later49, for its association with IR in Indian women with PCOS; the study suggested that CC genotype (C1085T) might be developed as a marker for IR and metabolic complications in Indian women48.…”
Section: Studies In the Genetics Of Pcos From Indiamentioning
confidence: 97%
“…MTORC2 is composed of mSIN1 and mLST8 and its core functional component, Rictor. Rictor regulates the functions of its downstream targets Akt, Rho, Rac and Cdc42, which themselves regulate egg cell survival and the construction of the cytoskeleton [ 18 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study was approved by the Shanghai Xinhua Hospital Research Ethics Board and all subjects gave their informed consent for inclusion before they participated in the study. Women were excluded if they had been diagnosed with 21-hydroxylase-deficiency, androgen-producing tumors, hyperprolactinemia, non-classical adrenal hyperplasia, Cushing's syndrome, and active thyroid disease, since these conditions likely affect reproductive physiology (19, 29). All the controls were defined as women with normal hormonal status and regular menstrual cycles at intervals of 28–35 days.…”
Section: Methodsmentioning
confidence: 99%
“…Related studies have been conducted on at least 70 genes, which roles are involved in the main process of this disease, such as steroid synthesis ( CYP11A1 and CYP19A1 ) (15), steroid action ( ESR1, ESR2 , and PGR ) (16), lipid metabolism ( PPARG and MTHFR ) (1719), insulin action ( HMGA2 ) (20) and embryonic development ( SUMO1P1 ) (21, 22) have been implicated in PCOS. However, the heterogeneity and generalizability of these genetic associations are not enough to explain clearly the considerable genetic susceptibility for this endocrine-metabolic disorder.…”
Section: Introductionmentioning
confidence: 99%